6x+6=-4x-24

Simple and best practice solution for 6x+6=-4x-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+6=-4x-24 equation:


Simplifying
6x + 6 = -4x + -24

Reorder the terms:
6 + 6x = -4x + -24

Reorder the terms:
6 + 6x = -24 + -4x

Solving
6 + 6x = -24 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
6 + 6x + 4x = -24 + -4x + 4x

Combine like terms: 6x + 4x = 10x
6 + 10x = -24 + -4x + 4x

Combine like terms: -4x + 4x = 0
6 + 10x = -24 + 0
6 + 10x = -24

Add '-6' to each side of the equation.
6 + -6 + 10x = -24 + -6

Combine like terms: 6 + -6 = 0
0 + 10x = -24 + -6
10x = -24 + -6

Combine like terms: -24 + -6 = -30
10x = -30

Divide each side by '10'.
x = -3

Simplifying
x = -3

See similar equations:

| -30j=22.5 | | x^2+1/3x+y^2-10/3y=127/9 | | 12f-2=25 | | -24=40t | | 142*2+4=180 | | 1/12+3/8y+5/12+5/8y | | v1/2=4 | | 3m-2/4=-5 | | -1/6y=-2/42 | | -10-6x=-28 | | -8+6x-3x=-26 | | 1/5(3x+4)-3/8(5-2x)=5(2x-7) | | -1-6(-b-4)=8b+7 | | h+12-5h=28 | | (x)-7=50 | | 3+2n+3n=10+6n | | (4/7y)^2 | | 4*0=5*0 | | 5/3p=-40 | | 9-(-3V-9)=54 | | 45=10x+15 | | 2(y+3)=3y+7 | | n-7=3-4n | | X=10-1/3y | | 5(3+7x)=-2x+15 | | 69(2x+4)=180 | | 10z-4+(k+11)=8k-7 | | T+12.7=-7.4 | | 15g-14g=16 | | 14x+4y+20+16x-5y-18= | | 9-(3V-9)=54 | | 142(2x+4)=180 |

Equations solver categories